OPTIMALISASI PEMBERDAYAAN MASYARAKAT MELALUI PENERAPAN PHBS DAN SENAM SEHAT SEBAGAI UPAYA PENINGKATAN KUALITAS HIDUP LANSIA SEJAHTERA DI DESA SUNGAI RAYA RT/RW 001/004 KELURAHAN SEMBULANG KECAMATAN GALANG - Zamzam Andrian Sigit; Nurhafizah Nasution; Mutia Amalia Lubis; Wa Diana; M. Fadli; Rizki Chandra Nugraha (Pusat Riset dan Inovasi Nasional, 2022)
Clean and Healthy Living Behavior is a behavior or action to strive for cleanliness and health from one's own volition and transmit it to others. This behavior includes maintaining personal hygiene and health so that it has an impact on the health of others and the surrounding environment which is one of the keys to achieving individual and public health status in Indonesia. Providing counseling is carried out based on the characteristics of the elderly who easily experience a decline in health and have difficulty doing activities so that they require assistance, management of health conditions so that they remain healthy and able to carry out activities properly. One of the solutions to problems that can be done to help improve understanding of the health of the elderly regarding healthy living behaviors and degenerative diseases is to provide counseling on clean and healthy living behaviors as early detection of non-communicable diseases. Prasetya & Noerfitri, 2023 stated that the family has an important role in improving the quality of public health, because in the family there is communication and interaction between family members which is an important start in a behavioral education process. The ten household PHBS indicators are births assisted by health workers, exclusive breastfeeding, weighing toddlers, using clean water, washing hands, using latrines, eradicating larvae, consuming fruit and vegetables, physical activity and not smoking in the house.